Analysis of Cross-Cultural Communication Barriers (Case Study of Husband and Wife of Sasak Tribe and Samawa Tribe in Poto Tano District, West Sumbawa Regency) - Riski Agustini; Lalu Ahmad Taubih; Firdaus AM (CV. Abhinaya Indo Group, 2025)
This research is entitled